Characterization of NOx-Ox relationships during daytime interchange of air masses over a mountain pass in the Mexico City megalopolis. (March 2018) - García-Yee, J.S.; Torres-Jardón, R.; Barrera-Huertas, H.; Castro, T.; Peralta, O.; García, M.; Gutiérrez, W.; Robles, M.; Torres-Jaramillo, J.A.; Ortínez-Álvarez, A.; Ruiz-Suárez, L.G.
Abstract: The role of the Tenango del Aire mountain pass, located southeast of the Mexico City Metropolitan Area (MCMA), in venting the city's air pollution has already been studied from a meteorological standpoint. To better understand the transport of gaseous air pollutants through the Tenango del Aire Pass (TAP), and its influence on the air quality of the MCMA, three mobile air quality monitoring units were deployed during a 31-day field campaign between February and March of 2011. Surface O3, NOx, and meteorological variables were continuously measured at the three sites. Vertical profiles of O3 and meteorological variables were also obtained at one of the sites using a tethered balloon. Days were classified as being under low pressure synoptic systems (LPS, 13 days), high pressure synoptic systems (HPS, 13 days), or as transition days (TR). The Mexican ozone standards at the Pass were not exceeded during LPS days, but were exceeded on almost all HPS days. A detailed analysis was performed using data from two typical days, one representative of LPS and the other of HPS. In both cases, morning vertical profiles of O3 showed a strong thermal inversion layer and near-surface O3 titration due to fresh NOx . In the LPS early morning, a single O3 layer of close to 45 ppb was observed from 150 to 700 magl. In the HPS early morning, 50 ppb was observed from 150 to 400 magl followed by a 400-m-thick layer with up to 80 ppb. These layers were the source of the morning increase of O3, with a simultaneous sharp decrease of NOx and CO as the mixing layer started to rise. During the LPS day, a southerly wind dominated throughout most of the daytime, with surface O3 lower than 60 ppb. The same was observed for the well-mixed midday and afternoon vertical profiles. Under HPS, northerly winds transported photochemically active air masses from the MCMA all morning, as observed by a smoother increase of Ox and O3, reaching 110 ppb of O3. Just after midday, the wind shifted back, carrying high-O3 (100–110 ppb) aged air masses until sunset. In addition, the midday and afternoon vertical profiles showed well-mixed high-O3 (100–110 ppb) mixing ratios. Analysis of Ox -NOx correlations was performed for these peri-urban and MCMA sites. A parallel analysis for the nearest urban air quality monitoring station in the MCMA was also done. A comparison allowed us to distinguish between photochemically active (VOC sensitive) or aged parcels (NOx sensitive) arriving at the TAP. Separating the correlations into time groups associated with wind direction changes allowed us to better distinguish between local, MCMA, or regional influence. The results are relevant to air quality management in the Mexico City megalopolis. Highlights: Low pressure systems drive O3 <70 ppb in clean air into the Valley of Mexico by Tenango del Aire Pass. High pressure systems drive O3 >100 ppb air back to into the Valley of Mexico by Tenango del Aire Pass. (Ox, NOx ) at Tenango del Aire Pass show moderate to high Ox with low NOx indicating aged air masses. In rural areas, south to MCMA, O3 7 h moving average >70 ppb several hours on high pressure days. Crops and forests south to MCMA, are exposed to severe exceedances of their AOT40 critical level.